Estrategias para la Divulgación (2013)
GEON journal is born from the needs of the academy to have publication spaces related to the areas of study of Administration and Business. The initiative, responsibility of the Faculty of Economic Sciences of the University of the Llanos, will have sections for the publication of constructs elements related to the Management, the Organizations and the Businesses. Although these are the central thematic axes, GEON opens an editorial space for the publications of professors, graduates, undergraduate and postgraduate students and for the productive sector to find a relevant academic space to interact with expressions that help to strengthen the integral formation of the professionals of the Region